Intermodal competition between intercity buses and trains: A theoretical model - Cornelia Gremm; David Bälz; Chris Corbo; Kay Mitusch (Karlsruher Institut für Technologie (KIT), Institut für Volkswirtschaftslehre (ECON), 2019)
The intercity bus market in Germany was deregulated in 2013. As a consequence, there is now a dense network of intercity bus lines. For the first time, the German state-owned railway company Deutsche Bahn AG faces intermodal competition in public intercity passenger land transport on a large number of lines. This paper examines market entry factors for intercity bus companies and price reactions of the incumbent railway company from a theoretical perspective. Our model builds on Salop's circular city model to describe the horizontal product differentiation among the bus companies. At the same time, the railway company occupies the center of the circle and offers a higher product quality than the buses. It dominates the market, while a number of bus companies constitute an oligopolistic competitive fringe. In the subsequent comparative statics analysis, it is shown that the quality differential between the train and bus services have a considerable effect on market entry decisions by buses as well as on price reactions by the incumbent railway company. In particular, on routes where the quality advantage of railway services is rather small, buses are more likely to enter and the railway company will respond with a stronger price reduction than on other routes.
Keywords: R40; L11; L13; 330; intermodal competition; intercity railway and bus services; Salop circle model with center; vertical and horizontal product differentiation; dominant firm with oligopolistic fringe